Strategi Manajemen Pembelajaran Al-Qur’an Berbasis Tutor Sebaya dalam Meningkatkan Kompetensi Baca Al-Qur’an - Tisnawati, Tri Endang; Putri, Zahra Alfina; Defriani; Fadillah, Nurul; Rizqa, Miftahir (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study aims to analyze peer tutoring as a management strategy for Qur’an learning in improving students’ Qur’anic reading competence through a library research approach. The analysis focuses on how peer tutoring is planned, organized, implemented, and supervised within the learning management system of schools or madrasahs. A review of relevant literature indicates that peer tutoring, when systematically managed through tutor selection, basic training, structured learning schedules, and teacher supervision, effectively enhances students’ mastery of hijaiyah letters, accuracy of makhraj, and reading fluency. In addition to technical skills, the strategy positively influences affective aspects such as learning motivation, confidence, and active participation. From a management perspective, peer tutoring optimizes limited instructional time, distributes learning responsibilities, and strengthens collaborative learning culture. The findings suggest that peer tutoring is not merely a pedagogical technique, but a practical and efficient learning management strategy that supports the effectiveness and sustainability of Qur’an education, particularly in institutions facing large class sizes and limited teacher availability. Penelitian ini bertujuan untuk menganalisis strategi manajemen pembelajaran Al-Qur’an berbasis tutor sebaya dalam meningkatkan kompetensi baca Al-Qur’an melalui pendekatan penelitian kepustakaan. Kajian ini menitikberatkan pada aspek perencanaan, pengorganisasian, pelaksanaan, dan pengawasan tutor sebaya sebagai bagian dari sistem pengelolaan pembelajaran di sekolah atau madrasah. Hasil telaah literatur menunjukkan bahwa tutor sebaya yang dikelola secara sistematis—melalui seleksi tutor, pembinaan dasar, penjadwalan kegiatan, serta supervisi guru—berkontribusi signifikan terhadap peningkatan penguasaan huruf hijaiyah, ketepatan makhraj, dan kelancaran membaca siswa. Selain aspek teknis, strategi ini juga berdampak positif pada motivasi, rasa percaya diri, dan keterlibatan aktif siswa. Dari perspektif manajemen pendidikan Islam, tutor sebaya menjadi solusi efektif untuk mengoptimalkan waktu guru, mengatasi keterbatasan sumber daya, dan membangun budaya belajar kolaboratif. Dengan demikian, tutor sebaya merupakan strategi manajerial yang relevan dan berkelanjutan dalam meningkatkan mutu pembelajaran Al-Qur’an.